Limiting the fault current of a wind turbine driven doubly fed induction generator system using fuzzy resistance limiter - Thapaliya, Sudeep (Brac University, 2024)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2022.